Charming and Praying: the Soft Power in the Lithuanian Charms - Vaitkevičienė, Daiva (Tautosakos darbai, 2022)
For a long time, folklore researchers from various countries struggled to determine if charms and prayers belonged to the same folklore genre, or two different ones. In Lithuania, this question used to be discussed in somewhat smaller extent, mainly concentrating on the comparison between charms and prayers addressed to the deities of the ancient Lithuanian religion (Žemyna, Gabija, the New Moon, etc.). The goal of this article is clarifying the features that enable establishing affinity between charms and prayers to gods, and what this says regarding the interconnection between these genres. Having discussed the problematic terminology in the 20th century Lithuanian folklore research, the author goes on to analyze the charms that are characterized by direct addressee and peculiar form of communication akin to prayers, namely employing the soft power, i. e. the action strategy based on mutual agreement. Such kind of charms in the article are defined as soft.According to the author’s research, soft charms display numerous features characteristic to the prayers addressed to gods; in terms of communication, such common components as direct address, exaltation, formulaic invitations and offerings, and requests for help can be discerned. Although some of these features are less pronounced in charms than in prayers, it still seems obvious that the soft charms and prayers constitute the same corpus of texts. Distinction between these genres could perhaps be sought only on the performative level, i. e. by analyzing the way and circumstances of uttering charms and prayers.
Keywords: charms; prayers; Baltic religion; magic; ethnomedicine